(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
This paper pays attention to the socio-economic aspect of the so-called “new international division of labour” or “global value chains” from a gender perspective. It analyses the garment industry and the prison labour known as “prison industrial complex” as part of the structuring and the division of labour on a global scale. Drawing from theories and research on global development, neo-marxist feminist theory, as well as the current events taking place in the economy and labour market, this work argues that the “new” international division of labour is unsustainable and harmful for women around the world in particular and for all socially vulnerable categories of people in general. At the same time, this paper presents the necessity for a gender sensitive policy-making that takes into account the specific context which both women and men are situated in, as well as the specific gendered effects emerging from the socio-economic politics of global development.